PENGARUH PENDEKATAN OPEN-ENDED TERHDAP HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 8 SAROLANGUN - Ferinaldi (Matedukasia, 2016)
This research is motivated by the low student learning outcomes. One of the contributing factors is the lack of an applied learning model, the teacher has not been able to attract students to try to participate actively, so students do not have initiative both intellectually and emotionally. Learning outcomes of most students did not reach KKM 7.50. This study aims to determine the effect of the Open-Ended approach on student learning outcomes. This research is a quantitative research, with a type of experimental research. The population of this study is all eighth grade students at Sarolangun Middle School 8 in the 2013/2014 academic year. The sample is class VIIIA control class and class VIII C as the experimental class. first tested the question instrument, namely the validity test, difficulty index, different power test, reliability test ,. then the data were analyzed using normality and homogeneity tests on the variance of the two samples. The results of the study showed that the average value of the experimental class was 81.84 and the control class was 74.06. Then the data were analyzed using parametric statistical test, namely the t test can be tcount  = 10.76 then compared with ttable  at a significant level of 0.05 obtained by ttable 2.00. so 10.76> 2.00 then Ha is accepted and Ho is rejected. This means that there is a positive influence between the Open-Ended approach and the learning outcomes of class VIII SMP Negeri 8 Sarolangun Academic Year 2013/2014. The results of learning Mathematics using the Open-Ended approach are better than the mathematics learning outcomes using conventional learning models of class VIII SMP Negeri 8 Sarolangun Academic Year 2013/2014.